Evaluasi Dampak Program Bimbingan Konseling Terhadap Perilaku Siswa - Fransiska, Devi; Abdullah, Haris (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The results of this research were carried out with the aim of being able to find out the role of guidance and counseling at SMPN 4 Metro in evaluating the behavior of students at SMPN 4 Metro. In this case, there are things that need to be paid attention to in evaluating in terms of management, service programs, teaching activities, activity evaluation, services for analyzing evaluation results at SMPN 4 Metro, all of these programs have been programmed at SMPN 4 Metro to be able to make students at school active in teaching and learning activities. Therefore all of these programs are run well so that they can find out the results from activeness in learning and BK teachers can evaluate students who are competent and not in learning and can understand the character of these students to make it easier for BK teachers to analyze the potential possessed by students.